Herbage Characteristics of Pintoi Peanut and Paslisadegrass Established as Monoculture or Mixed Swards. Issue 5 (2nd July 2018) - Alencar, N. M.; Vendramini, J. M. B.; dos Santos, A. C.; Silveira, M. L.; Dubeux, J. C. B.; Sousa, L. F.; Neiva, J. N. M.
Abstract : Pintoi peanut ( Arachis pintoi Krapovickas & Gregory) is a warm‐season perennial legume that has been used in grass–legume mixtures; however, management practices to successfully establish pintoi into warm‐season grass swards have not been fully examined. Two experiments were conducted to evaluate different sward compositions and methods of establishment of pintoi peanut or pintoi peanut–palisadegrass [ Urochloa brizantha (A. Rich.) R.D. Webster] mixed swards. The first experiment evaluated pintoi peanut and palisadegrass established as monocultures or in a pintoi peanut–palisadegrass mixture. Pintoi peanut ground cover and density was greater for pintoi peanut than pintoi peanut–palisadegrass mixed swards (29 vs. 8%, and 42 vs. 19 plants m −2 for ground cover and density, respectively). Concomitant seeding of pintoi peanut and palisadegrass showed no negative effect on palisadegrass herbage mass (HM). In the overseeding experiment, treatments were: (i) peanut interseeded into glyphosate‐treated rows subsequently strip tilled into prepared seedbed strips (0.4 m) with intervening untilled areas (2 m); (ii) peanut no‐till seeded into glyphosate‐treated rows (0.4 m) with intervening untilled areas (2 m); and (iii) an undisturbed sward of palisadegrass with no pintoi peanut. Prepared seedbed and no‐till treatments had similar pintoi ground cover (2.9%), density (8.7 plants m −2 ), spread (11.7 cm), and HM (170 kg ha −1 yr −1 ). Glyphosate treatment of rows followed by no‐till seeding was an effective strategy to establish pintoi peanut into palisadegrass swards. Pintoi peanut contribution during the early stages after establishment is insufficient to generate sufficient biological N fixation and produce forage for livestock.